Utilization of Social Media Instagram As A Promotion Means For the Special Library of the Bank Indonesia Representative Office of South Sumatera Province Through Digital Content - Solehati, Indah; Rohmaniyah, Rohmaniyah (UIN Raden Intan Lampung, 2025)
This study explores the utilization of Instagram as a promotional tool at the Special Library of the Bank Indonesia Representative Office in South Sumatra Province. The main objective of this research is to examine how Instagram is strategically used to introduce library services, enhance public economic literacy, and build a positive institutional image through various forms of digital content. This study employs a qualitative approach with data collection techniques that include direct observation of the Instagram account @perpustakaan_bi_sumsel, interviews with librarians responsible for social media management, and documentation of published content. The findings reveal that the library utilizes a variety of digital content formats such as photos, videos, podcasts, and educational quizzes to deliver information to users. The content includes book reviews, Reader of the Month features, Bank Indonesia scholarship information, as well as financial literacy and payment system materials. The use of Instagram has proven effective in attracting public interest—particularly among younger audiences—to engage with the library both physically and virtually. The informative and educational communication strategies implemented through social media also contribute to increased public participation in economic literacy initiatives and broaden the reach of library services. Thus, the use of Instagram as a promotional medium has significantly contributed to enhancing the visibility and appeal of the library in the digital age.